Trajectories of Care: Representations of Empowered Mothering in Contemporary Bollywood - Pramanik, Pratyusha; Mishra, Ajit K. (University of Malaya, 2023)
Recent cinematic representations in Bollywood have witnessed an ongoing shift of depicting mothers who are disrupting the dominant discourses of mothering practices prevalent in India. This changing discourse of motherhood and its representation has also brought to light the challenges that these mothers face while practicing these changes, and the strategies they adopt to overcome these challenges. While catering to the needs of a child with disability, the mother assumes the role of the nurse, the therapist, and the educator and their caregiving responsibilities are manifold as compared to mothering a child with normative needs. Uninterrupted care work, societal surveillance and prevalent stigma severely interfere with the mental, physical, and existential well-being of such mothers. Through a thematic analysis of The Sky is Pink (dir. Bose, 2019), and Jalsa (dir. Triveni, 2022), this article maps the trajectories of care and examines the alternative mothering strategies adopted by mothers of children with disabilities to take care of their children and themselves. A critical examination of these on-screen mothers provides an insight into the individual care needs of the caregiver and the care receiver.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Children with Disabilities; Chronic Sorrow; Empowered Mothering; Good/Bad Mother; Parental Burnout